Frequency of 6-thioguanine-resistant T cells is inversely related to the declining T-cell activities in aging mice. - Inamizu, T (1986)
The frequency of clonable 6-thioguanine-resistant (6-TGr) splenic T cells increased moderately with age in female BALB/c mice ranging in age from 3 to 32 months; however, the correlation between the frequency of clonable 6-TGr cells and age was weak. Those clonable 6-TGr T cells were deficient in hypoxanthine/guanine phosphoribosyltransferase (HGPRT) activity and sensitive to hypoxanthine/aminopterin/thymidine medium, as in the case of HGPRT-deficient L5178Y mouse lymphoma cells. When splenic T cells of individual aging mice were assessed simultaneously for the frequency of clonable 6-TGr T cells and for their ability to produce interleukin 2 or to proliferate in response to mitogenic stimulation, an inverse correlation was observed. These results indicate that the frequency of 6-TGr T cells is more closely related to physiologic age than chronologic age. This would mean that the frequency could be used as an index of physiologic age and that the T cells could serve as a cellular model relating gene alterations to physiologic age.